Factors that influence Home IoT adoption among Ipoh, Perak citizens - Christopher Cho Wen Xuan; Juzaimi Nasuredin (Research in Management of Technology and Business, 2023)
The Internet of Things (IoT) was developed continuously and extended to other fields’ use. Home IoT is a domestic appliance with internet connectivity (enabled with sensors, controllers, and communication systems) to allow users to control the object and adapt to their needs. It has become a trend to use worldwide and grow continuously. Previous research indicated a need for a comprehensive IoT ecosystem, no standardization in Home IoT technology, and fewer concerns about the level of security and privacy in the country were barriers to current IoT adoption in Malaysia. The factor influencing Home IoT adoption should be studied to explore the potential of adopting Home IoT in Ipoh, Perak citizens. Therefore, this study purposely investigates the relationship between perceived usefulness, perceived ease of use and perceived risks to the adoption level of Home IoT in Ipoh, Perak citizens. A quantitative research survey was used for data collection. Descriptive statistical analysis and correlation analysis were used to analyze the collected data results using SPSS software (Statistical Package for the Social Sciences). The results of the correlation analysis show that perceived usefulness and perceived ease of use had a significant positive relationship with the adoption level of Home IoT; Meanwhile, perceived risk had a significant negative relationship with the adoption level of Home IoT. Therefore, understanding the factors that impacted the adoption of Home IoT can help related parties to improve the adoption of Home IoT in Ipoh, Perak citizens. Further study can express more dimensional factors and expand the scope of research.